2017
DOI: 10.1016/j.stemcr.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Human Neural Stem Cell Transplantation Dose Alters Oligodendroglial and Neuronal Differentiation after Spinal Cord Injury

Abstract: SummaryMultipotent human central nervous system-derived neural stem cells transplanted at doses ranging from 10,000 (low) to 500,000 (very high) cells differentiated predominantly into the oligodendroglial lineage. However, while the number of engrafted cells increased linearly in relationship to increasing dose, the proportion of oligodendrocytic cells declined. Increasing dose resulted in a plateau of engraftment, enhanced neuronal differentiation, and increased distal migration caudal to the transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 53 publications
1
35
0
Order By: Relevance
“…Colored outlines of the initial dose of SC121 + cells. (C) No difference was found between the proportion of SC121 + /Ki67 + cells in each dose group after normalization to total number of SC121 + cells (previously published in (Piltti et al Submitted); Mean ± SEM, 1-way ANOVA p =0.28. However, (D) correlation analysis revealed a significant negative relationship between increasing cell dose and the proportion of SC121 + /Ki67 + donor cells; Pearson r= −0.55, p ≤0.01.…”
Section: Figurementioning
confidence: 62%
See 2 more Smart Citations
“…Colored outlines of the initial dose of SC121 + cells. (C) No difference was found between the proportion of SC121 + /Ki67 + cells in each dose group after normalization to total number of SC121 + cells (previously published in (Piltti et al Submitted); Mean ± SEM, 1-way ANOVA p =0.28. However, (D) correlation analysis revealed a significant negative relationship between increasing cell dose and the proportion of SC121 + /Ki67 + donor cells; Pearson r= −0.55, p ≤0.01.…”
Section: Figurementioning
confidence: 62%
“…Scale bars 300 μm (low mag) and 50 μm (high mag). Estimated total number of hCNS-SCns positive for SC121 (bars shaded to indicate dose) were significantly greater in the very high dose group when compared to the low or medium dose groups (B) at 2 WPT or (C) 16 WPT ; Mean ± SEM, 1-way ANOVA p =0.009 (previously published in (Piltti et al Submitted); 1-way ANOVA p =0.0002, respectively. Tukey’s t-test p values are shown in the graphs.…”
Section: Figurementioning
confidence: 66%
See 1 more Smart Citation
“…They found that locomotor improvements were abolished when transplanted cells were rendered unable to myelinate (Hawryluk et al, ; Yasuda et al, ) supporting a role of myelinogenesis by transplanted cells in driving improved recovery. Likewise, transplantations with enhanced oligodendrocyte differentiation over naïve NPCs have been associated with improved myelination and locomotor function, indicating forming oligodendrocyte lineage cells may be particularly advantageous (Cao et al, ; Hofstetter et al, ; Hwang et al, ; Piltti et al, ). Whether transplanted oligodendrocytes enhance spared white matter via direct trophic support of axons remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Two‐ to six‐months following transplantation, counts of surviving cells ranged from less than 1% to as high as 23.9% . Another study observed a plateau of approximately 400,000 surviving human cells within the spinal cord, regardless of initial dose . Although the vast majority of transplanted cells remain within the transplantation site, there have been reports of migration more than 7 mm distal to the site of transplantation, corresponding to approximately 3 vertebrae .…”
Section: Human–animal Chimerismmentioning
confidence: 99%